2021
DOI: 10.3389/fpsyg.2021.705336
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Teachers' and Their Students' Social and Emotional Learning During the “Learning to Be Project”-Training Course in Five European Countries

Abstract: In recent years, the school curricula in many European countries have introduced social and emotional learning (SEL). This calls for the teachers to have SEL competencies. The present study evaluates teachers' and their students' readiness for SEL during an intervention in five European countries. The participants were teachers (n = 402) in five European countries; Italy, Latvia, Lithuania, Slovenia, and Spain. The pre- and post-measuring points for both the intervention and the comparison group were at approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…It is also possible that students' SEL develops only partially. In our previous study, even 8-11 old students developed only in their intrapersonal competence, namely, self-awareness and self-management (Berg et al, 2021). Interestingly, both above-mentioned results (Corcocan et al, 2018;Larsen et al, 2021) were collected among teenagers.…”
Section: Are the Outcomes Of Sel Related To The Age Of The Students?mentioning
confidence: 82%
See 1 more Smart Citation
“…It is also possible that students' SEL develops only partially. In our previous study, even 8-11 old students developed only in their intrapersonal competence, namely, self-awareness and self-management (Berg et al, 2021). Interestingly, both above-mentioned results (Corcocan et al, 2018;Larsen et al, 2021) were collected among teenagers.…”
Section: Are the Outcomes Of Sel Related To The Age Of The Students?mentioning
confidence: 82%
“…Regarding SEL skills, Corcoran, Cheung et al (2018) stated that even the most popular SEL approaches used at school do not always present strong evidence of effectiveness in learning SEL. For example, our own international study in five EU countries showed that after the SEL intervention the favourable outcomes took place only among 8-11 years old students but nor among teenagers (Berg et al, 2021). It is also possible that students' SEL develops only partially.…”
Section: Are the Outcomes Of Sel Related To The Age Of The Students?mentioning
confidence: 98%
“…Although comprehensive SEL programs have recently been developed to promote SEL in schools across Europe also (see, for instance, Agliati et al, 2020 ; Berg et al, 2021 ; Cefai et al, 2022 ), there is currently a lack of validated measures for evaluating SEL in European countries ( Anthony et al, 2022a ). A recent review ( Cavioni and Grazzani, 2023 ) identified one exception to this pattern: the Devereux Student Strengths Assessment (DESSA) battery, which was first standardized in the United States ( LeBuffe et al, 2014 ) and then adapted for use in Italy.…”
Section: What Is Social and Emotional Learning?mentioning
confidence: 99%
“…Research has found that supporting the development of teachers' social and emotional skills - such as the ability to recognize and regulate their own emotions (particularly anxiety and stress), collaboration, empathy, self-efficacy, and the ability to seek and maintain social support - increase their wellbeing (Pulido-Martos et al, 2016 ; Collie et al, 2020 ; Mariani et al, 2020 ; Ornaghi et al, 2022 , 2023 ). In turn, positive effects may be visible also on students' achievements, motivation, school belonging, and mental health (Harding et al, 2019 ; Berg et al, 2021 ; Cefai et al, 2022 ). While previous research has recognized the importance of focusing on teachers' wellbeing (Cavioni et al, 2020 ; Lester et al, 2020 ; Hascher et al, 2021 ), still limited attention has been given to the development and implementation of targeted interventions that directly address the unique challenges faced by educators (Cavioni et al, 2023b ).…”
Section: Introductionmentioning
confidence: 99%